Utilization of Banana (Musa acuminata) Pseudostem for Biscuit Making - Maskey, Bunty; Sangroula, Pradeep; Shrestha, Nabindra Kumar (Himalayan Journal of Science and Technology, 2020)
The aim of this research was to utilize banana pseudostem powder as a functional replacement ingredient for wheat flour in the production of biscuit. In this study, D-optimal mixture design was employed and five different formulations were obtained. The biscuits were prepared by partially replacing wheat flour with banana pseudostem powder from 0-10% and investigated for sensory and quality attributes. The biscuits were subjected to sensory evaluation by ten semi-trained panelists for consumer acceptability. The data obtained were statistically analyzed using two-way ANOVA (no blocking) at 5% level of significance. From the mean sensory scores, 2.5 parts pseudostem incorporation was selected as the best formulation and subjected for further proximate analysis. The calcium, potassium, sodium, ash, fibre and fat contents were found to be higher in banana pseudostem incorporated biscuit than wheat flour biscuit.